Music as a Tool of Political Activisim in Nigeria: A Case Study of Fela Anikulapo Kuti. Journal Eduvest - Augustus Fisher; Sobulo Abdullahi Idowu (Eduvest - Journal of Universal Studies, 2023)
Music has been a significant tool of political activism in the world. Music tends to pass emotions, motivate and inspire political consciousness. This study examines the impact of music on political activism in Nigeria using Fela Anikulapo Kuti as a case study. The secondary method of data collection and analysis is adopted to gather information. The study presents that, indeed, music is a relevant tool of political activism. Music has been used to advocate political ideology and improve consciousness. Fela Anikulapo Kuti is an iconic political activist in Nigeria using music as a tool to lead his political activism